2020
DOI: 10.3389/fphar.2020.01238
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammasome Signaling Proteins ASC and IL-18 as Biomarkers of Psoriasis

Abstract: Inflammasome activation in the innate immune response plays a role in the pathogenesis of psoriasis largely due to the increased levels of pro-inflammatory cytokines. However, the precise role of inflammasomes in psoriasis (Ps) and psoriatic arthritis (PsA) is largely undefined. To establish the reliability of inflammasome signaling proteins as diagnostics and predictive biomarkers of clinical severity in this disease population, serum from healthy donors and patients with Ps/PsA were analyzed for the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 29 publications
8
31
0
Order By: Relevance
“…It is also critical to establish how these processes affect the inflammatory milieu in the thrombus microenvironment and in the systemic inflammatory response after cerebral ischemia. However, we have previously shown secreted inflammasome proteins caspase-1, ASC, IL-1β and IL-18 correlate with poorer outcomes in a variety of diseases or conditions of the nervous system and periphery, suggesting that these secreted inflammasome proteins are functional in inflammasome signaling ( Kerr et al, 2018a ; Kerr et al, 2018b ; Keane et al, 2018 ; Forouzandeh et al, 2020 ; Perez-Barcena et al, 2020 ; Scott et al, 2020 ), suggesting an important role in disease- or trauma-related inflammatory pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…It is also critical to establish how these processes affect the inflammatory milieu in the thrombus microenvironment and in the systemic inflammatory response after cerebral ischemia. However, we have previously shown secreted inflammasome proteins caspase-1, ASC, IL-1β and IL-18 correlate with poorer outcomes in a variety of diseases or conditions of the nervous system and periphery, suggesting that these secreted inflammasome proteins are functional in inflammasome signaling ( Kerr et al, 2018a ; Kerr et al, 2018b ; Keane et al, 2018 ; Forouzandeh et al, 2020 ; Perez-Barcena et al, 2020 ; Scott et al, 2020 ), suggesting an important role in disease- or trauma-related inflammatory pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that inflammasome proteins are good inflammatory biomarkers of traumatic brain injury, 16 , 36 stroke, 15 psoriasis, 37 and multiple sclerosis, 14 as well as mild cognitive impairment (MCI) and AD. 38 Interestingly, it has been suggested that AMD and AD share a common pathologic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings indicate that inflammasome signaling pathway proteins, such as IL-18 and ASC, play a crucial role in inflammatory responses associated with psoriasis pathology. In the future, these proteins could be key biomarkers that help determine the diagnosis of psoriasis in this patient population [ 35 ].…”
Section: The Nlrp3 Inflammasome (In Psoriasis)mentioning
confidence: 99%